2019
DOI: 10.1590/s0102-865020190120000004
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of adenosine on experimentally induced acute ulcerative colitis model in rats

Abstract: Purpose: To examine the therapeutic effect of external adenosine on an acetic acid-induced acute ulcerative colitis model in rats. Methods:Thirty male mature rats were divided into three groups as control, acute colitis (AC) and AC+adenosine group (AC+AD). AC was induced by rectal administration of 4% acetic acid (AA). 5mg/kg/day adenosine was performed i.p for 4 weeks to AC+AD group. Rectum and colon were excised for microscopic and histopathological histopathologic evaluations, and immunohistochemical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…11,12 Previous studies have well documented that the compounds adenosine, uridine, and indirubin exhibit potent anti-colitis effects in different animal colitis models. [13][14][15][16][17] However, no evidence-based study has been conducted to assess the efficacy of BLG against colitis. In the present study, we investigated the protective effect of BLG on dextran sulfate sodium (DSS)-induced chronic relapsing colitis in C57BL/6 mice and found that oral administration of BLG significantly alleviated DSS-induced chronic relapsing colitis in mice, and its regulatory mechanism was associated with regulating gut microbiota and restoring gut derived-glucagon-like peptide-1 (GLP-1) production.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Previous studies have well documented that the compounds adenosine, uridine, and indirubin exhibit potent anti-colitis effects in different animal colitis models. [13][14][15][16][17] However, no evidence-based study has been conducted to assess the efficacy of BLG against colitis. In the present study, we investigated the protective effect of BLG on dextran sulfate sodium (DSS)-induced chronic relapsing colitis in C57BL/6 mice and found that oral administration of BLG significantly alleviated DSS-induced chronic relapsing colitis in mice, and its regulatory mechanism was associated with regulating gut microbiota and restoring gut derived-glucagon-like peptide-1 (GLP-1) production.…”
Section: Introductionmentioning
confidence: 99%
“…Some other experimental studies have been published using plant extracts and drugs for the treatment of UC, emphasizing other mechanisms as inhibiting the secretion of IL-13, increased immunoexpression of NF-kB in rectum, etc. 38 , 39 . The histopathologic and macroscopic validations of the scores used in the present study were based on previous methods 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The grading of colonic damage (ulceration, inflammation, depth of the lesion, and fibrosis) and the number of goblet cells were determined using a scale of Vilaseca as described in detail previously [37,54]. The standard techniques of staining of Caspase-3, PCNA, and NFkB were followed as provided by the instructors [1,18,59].…”
Section: Methodsmentioning
confidence: 99%